2017
DOI: 10.1038/s41598-017-03220-y
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial protease uses distinct thermodynamic signatures for substrate recognition

Abstract: Porphyromonas gingivalis and Porphyromonas endodontalis are important bacteria related to periodontitis, the most common chronic inflammatory disease in humans worldwide. Its comorbidity with systemic diseases, such as type 2 diabetes, oral cancers and cardiovascular diseases, continues to generate considerable interest. Surprisingly, these two microorganisms do not ferment carbohydrates; rather they use proteinaceous substrates as carbon and energy sources. However, the underlying biochemical mechanisms of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 65 publications
1
30
0
Order By: Relevance
“…Therefore, PeDPP11 in complex with a peptide was chosen as a template for the modeling routine. The coordinates of PeDPP11 in complex with the dipeptide Arg-Asp (PDB code: 5JWG) [22] were subjected to structural alignment and further model building.…”
Section: Modeling Of Bfdpp11mentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, PeDPP11 in complex with a peptide was chosen as a template for the modeling routine. The coordinates of PeDPP11 in complex with the dipeptide Arg-Asp (PDB code: 5JWG) [22] were subjected to structural alignment and further model building.…”
Section: Modeling Of Bfdpp11mentioning
confidence: 99%
“…We performed 3D modeling of BfDPP11 using the structure of PeDPP11 (PDB code: 5JXK) [22], which indicated that BfDPP11 also has a bilobal architecture with an entirely helical domain capping the catalytic domain bearing a typical chymotrypsin double β-barrel fold. PeDPP11 3D structures in complexes with peptides (5JY0, 5JWG, 5JWI, 4XZY) and PgDPP11 showed that the S1 subsite is formed by Arg 337 , His 649 , Thr 650 , Gly 652 , Asn 670 , Arg 673 , Gly 677 , Gly 680 , Asp 681 , and…”
Section: Bfdpp11 3d Structural Modeling and Mechanism Of Its Inefficimentioning
confidence: 99%
See 2 more Smart Citations
“…This enthalpy‐entropy compensation effect has been widely discussed as it was originally thought to be an experimental artifact 31 . However, this seems to be a phenomenon that occurs mainly in multimeric proteins when they bind to their ligands 32,33 . Conversely, the differences in affinity of the active sites in multimeric enzymes have been related to dynamic changes at the level of the secondary structure during the formation of the enzyme‐substrate complex.…”
Section: Resultsmentioning
confidence: 99%